Predicting the Holocaust : Jewish Organizations Report from Geneva on the Emergence of the "Final Solution," 1939-1942. - Matthäus, Jürgen (Documenting life and destruction., 2018)
This profoundly informed volume provides the first in-depth overview of Jewish assessments of the evolving Nazi Judenpolitik in the early years of World War II. Jürgen Matthäus showcases the perceptive reports compiled by two Geneva-based offices, among the first to predict the threat to millions of Jews with the rising tide of Nazi rule over Europe.